2015
DOI: 10.1111/ppa.12470
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and genetic structure of Fusarium graminearum species complex populations affecting the main barley growing regions of South America

Abstract: Members of the Fusarium graminearum species complex (FGSC), such as F. graminearum and F. asiaticum, are the main cause of fusarium head blight (FHB) of wheat and barley worldwide. In this study, 117 FGSC isolates obtained from commercial barley grain produced in Argentina (n = 43 isolates), Brazil (n = 35), and Uruguay (n = 39) were identified to species and trichothecene genotypes, and analysed using amplified fragment length polymorphism (AFLP) and sequence‐related amplified polymorphism (SRAP) markers. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The genomes of all the F. graminearum and F. poae screened for the potential production of DON and/or NIV became amplified positively for DON- and/or NIV-related sequences, as had been previously observed for Argentine isolates obtained from barley grains [ 29 , 30 , 34 ]. Therefore, since we isolated a high frequency of these Fusarium species from many samples, we could anticipate contaminations with these toxins as generated by those species.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The genomes of all the F. graminearum and F. poae screened for the potential production of DON and/or NIV became amplified positively for DON- and/or NIV-related sequences, as had been previously observed for Argentine isolates obtained from barley grains [ 29 , 30 , 34 ]. Therefore, since we isolated a high frequency of these Fusarium species from many samples, we could anticipate contaminations with these toxins as generated by those species.…”
Section: Discussionsupporting
confidence: 58%
“…Many studies have demonstrated a decrease in the quality of different cereals as a result of the presence of Fusarium species, even in the absence of contamination from the mycotoxins produced by this fungal genus; with wheat being the most extensively studied cereal at the global and national level [ 16 , 22 , 28 ]. Little is known, however, about the prevalence and diversity of Fusarium species or the accompanying presence of their mycotoxins through field studies on barley [ 8 , 20 ], mainly because the investigations at characterizing the Fusarium graminearum -species complex and its potential to produce toxins have been conducted in vitro [ 29 , 30 ]. Although few such studies have been performed on barley, the presence of Fusarium species on this cereal is known to affect different parameters for malting—e.g., the germination capacity of the grain and the increase in protein and nitrogen content [ 20 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, cereal industry efforts have largely focused on measuring DON because of its prevalence relative to NIV, despite the latter's higher toxicity. The importance of regional surveillance was recently highlighted in studies that reported significant proportion of NIV genotypes in F. graminearum species complex members infecting wheat in southern Brazil, but particularly barley at higher frequency of NIV-producing species than in wheat (Astolfi et al 2011;Del Ponte et al 2015;Castañares et al 2016). In fact, a threeyear survey of commercial wheat in southern Brazil showed the co-occurrence of DON and NIV in 90% of samples, at average levels of 540 and 337 μg/kg, respectively (Del .…”
Section: Successes and Future Challengesmentioning
confidence: 99%
“…In Brazil, molecular surveys since the mid-2000s have contributed to understanding FGSC diversity associated with FHB in wheat (Scoz et al, 2009;Astolfi et al, 2012;Del Ponte et al, 2015) and barley (Astolfi et al, 2011;Castañares et al, 2016;Machado et al, 2017). For those crops, F. graminearum is the dominant species from the FGSC (>80% frequency) along with four other DON-or NIVproducing species within the complex.…”
Section: Introductionmentioning
confidence: 99%